Perspectives on brain health and dementia prevention in Latin America: challenges and opportunities - Fox, Sarah; León, Tomás; Mariano, Luciano; Arshad, Faheem; Magrath Guimet, Nahuel; Hope, Grainne; Tituaña, Kuripacha; Zapata-Restrepo, Lina María (Frontiers in Dementia, 2023)
While age-specific dementia prevalence is falling in many countries, several recent reviews estimate prevalence in Latin America to be higher than anywhere else in the world. This may be, in part, due to the high incidence of socioeconomic and health-related risk factors present in the region. However, growing evidence suggests that primary and secondary prevention via modifiable risk factors is possible, and that 40% of cases may be mitigated through interventions which target modifiable risk. This suggests that there may be significant scope for dementia risk reduction in this region.